Cox Proportional Hazard Regression Model in Analysis of Factors Affecting Survival Time (Case Study: Lung Cancer Patients at RSUDZA Aceh) - Zakiah, Siti; Ramadhani, Evi; Safitri, Rini (Transcendent Journal of Mathematics and Applications, 2024)
Lung cancer is a significant global health challenge, including in Indonesia and especially in Aceh. This study uses survival analysis with a Cox proportional hazards regression model which aims to identify factors that influence the survival time of lung cancer inpatients at RSUDZA Aceh for the period January to December 2022. The results of the Cox proportional hazards regression model show that the factors are significant affecting survival time are chemotherapy and the type of cancer. Based on the hazard ratio value, it is known that patients who do not undergo chemotherapy have a two times higher risk of death compared to patients who undergo chemotherapy. In addition, patients with squamous cell carcinoma have a 0.5 times lower risk of death compared to patients who have adenocarcinoma.